Estimation of Winding Factors of Two-layer Three-phase Fractional Windings - Bukšnaitis, J. (Elektronika ir Elektrotechnika, 2009)
Estimation method of winding factors of the two-layer three-phase fractional windings is analyzed. It was proved by theoretical calculations that the analytical expression dedicated for the calculation of winding factors of the two-layer former three-phase windings can not be applied to calculate these factors of the odd and even harmonics of the two-layer former three-phase fractional windings. It can be explained by the fact that the numbers of the three-phase fractional winding coils in the sections are not equal and they do not match the number of the pole and phase slots. Since the single-layer concentrated and the two-layer former fractional (q  1/2) three-phase windings are similar because the relative magnitudes of the respective -th odd harmonics of their rotating magnetomotive forces are equal, thus the winding factors for all harmonics of two-layer three-phase fractional windings can be estimated only on the basis of the results of harmonic analysis of instantaneous rotating magnetomotive force function of the considered windings and two-layer former fractional (q  1/2) three-phase winding. Ill. 1, bibl. 5, tabl. 8 (in English; abstracts in English, Russian and Lithuanian).